Soticlestat, a novel cholesterol 24‐hydroxylase inhibitor, reduces seizures and premature death in Dravet syndrome mice. (12th September 2021) - Hawkins, Nicole A.; Jurado, Manuel; Thaxton, Tyler T.; Duarte, Samantha E.; Barse, Levi; Tatsukawa, Tetsuya; Yamakawa, Kazuhiro; Nishi, Toshiya; Kondo, Shinichi; Miyamoto, Maki; Abrahams, Brett S.; During, Matthew J.; et al.
Abstract: Objective: Dravet syndrome is a severe developmental and epileptic encephalopathy (DEE) most often caused by de novo pathogenic variants in SCN1A . Individuals with Dravet syndrome rarely achieve seizure control and have significantly elevated risk for sudden unexplained death in epilepsy (SUDEP). Heterozygous deletion of Scn1a in mice ( Scn1a +/− ) recapitulates several core phenotypes, including temperature‐dependent and spontaneous seizures, SUDEP, and behavioral abnormalities. Furthermore, Scn1a +/− mice exhibit a similar clinical response to standard anticonvulsants. Cholesterol 24‐hydroxlase (CH24H) is a brain‐specific enzyme responsible for cholesterol catabolism. Recent research has indicated the therapeutic potential of CH24H inhibition for diseases associated with neural excitation, including seizures. Methods: In this study, the novel compound soticlestat, a CH24H inhibitor, was administered to Scn1a +/− mice to investigate its ability to improve Dravet‐like phenotypes in this preclinical model. Results: Soticlestat treatment reduced seizure burden, protected against hyperthermia‐induced seizures, and completely prevented SUDEP in Scn1a +/− mice. Video–electroencephalography (EEG) analysis confirmed the ability of soticlestat to reduce occurrence of electroclinical seizures. Significance: This study demonstrates that soticlestat‐mediated inhibition of CH24H provides therapeutic benefit for the treatment of Dravet syndrome in mice and has the potential for treatment of DEEs.